2023
DOI: 10.3390/inorganics11090349
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of Open-Shell Metallofullerene Anions: Synthesis, Crystal Structures, and Electrochemical Properties of Benzylated Gd@C2v-C82

Xinyi Zhou,
Yang-Rong Yao,
Yajing Hu
et al.

Abstract: The reactivity of the open-shell Gd@C2v-C82 with different charge states towards benzyl bromide was investigated. [Gd@C2v-C82]3− exhibited enhanced activity relative to Gd@C2v-C82 and [Gd@C2v-C82]−. The structural characterizations, including MALDI-TOF MS, UV-vis-NIR, and single crystal X-ray diffraction, indicate the formation of isomeric benzyl monoadducts of Gd@C2v-C82. All three monoadducts contain 1:1 mirror-symmetric enantiomers. Additionally, the addition of the benzyl group and its specific position re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…However, the one-electron reduction of La@ C 2 v -C 82 is effective for the activating its reactivity toward alkyl halides in the thermal reaction. Recently, Zhou et al reported that the reaction of Gd@ C 2 v -C 82 with benzyl bromide requires a three-electron reduction of Gd@ C 2 v -C 82 for the addition reaction to occur at room temperature [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the one-electron reduction of La@ C 2 v -C 82 is effective for the activating its reactivity toward alkyl halides in the thermal reaction. Recently, Zhou et al reported that the reaction of Gd@ C 2 v -C 82 with benzyl bromide requires a three-electron reduction of Gd@ C 2 v -C 82 for the addition reaction to occur at room temperature [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…Lowering the reaction temperature requires an increase in the reactivity of EMF anions, which can be achieved by the reduction beyond the monoanionic state. Li et al showed that benzyl bromide reacts with the Gd@C 2v (9)-C 82 3trianion already at room temperature to give several isomers of Gd@C 82 (CH 2 Ph) [117].…”
Section: Redox-extraction and Derivatization Of Anionsmentioning
confidence: 99%